THE DEVELOPMENT OF TEXTBOOK INTEGRATED IMTAK ON VERTEBRATE MATERIAL FOR SENIOR HIGH SCHOOL GRADE 10th - Husfina Suaidah; Reni Ambarwati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Abstract Integrated Islamic School which promote spiritual competences has a great demand among the community because it can develop children's morals, beside of emphasizing the mastery of science that is needed in the global development. Integration between Islamic values ​​in Qur'an which mention animals, included Vertebrate can be done to instill spiritual values ​​and character if it interpreted properly. However, the textbook which integrates both was not available yet. This research aimed to develop textbook integrated religious values on Vertebrate material which fulfills validity and practicality. This research was referred to 4D development model (define, design, develop, and disseminate), but disseminate phase was not done. The development of this textbook was conducted in the Biology Department FMIPA UNESA and the limited trial was conducted on 20 students in MAN Sidoarjo 10th grade. The validity of the textbook was determined based on the assessment done by three experts, who are biology educational expert, animal taxonomy expert, and Islamic religious expert. The practicality of the textbook was determined based on the readability test by using Fry Graph, the implementation of learning, and the student responses. Data were analyzed descriptive-quantitatively. The validity of textbook in terms of the content, appearance, linguistic, and integration components of IMTAK got an average of 98,81%, indicated very valid category, so it was suitable to be used in learning. The practicality of textbook based on the readability test using Fry Graph showed the level of readability at level 10, implementation of textbook in learning was 97,5%, indicated very good category, and students positive responses to the textbook got an average of 99.5%, indicated very good category, so the textbook was practical to be used in learning. Hence, the textbook integrated IMTAK on Vertebrate material was declared valid and practical to be used in biology learning. Key Words: textbook, IMTAK integration, vertebrate.